2011
DOI: 10.1111/j.1570-7458.2011.01131.x
|View full text |Cite
|
Sign up to set email alerts
|

Preference for feeding on honey solution and its effect on survival, development, and fecundity of Ebrechtella tricuspidata

Abstract: Members of the spider families Thomisidae, Salticidae, Miturgidae, Anyphaenidae, and Corinnidae have been observed on floral and extrafloral nectaries of plants, where they are presumably feeding on nectar. Nectar feeding is a phenomenon that has long intrigued biologists. However, few studies have focused on the effect of nectar on biological characteristics of these spiders. The aim of this study was to determine whether crab spiders, Ebrechtella tricuspidata (Fabricius) (Araneae: Thomisidae), show an active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…In the miturgid spider, Cheiracanthium inclusum , supplementing the diet of food-limited individuals with nectar allows them to achieve growth and reproductive rates comparable to individuals fed higher quantities of prey (Taylor and Pfannenstiel 2009). Similar results have been found in the crab spider Ebrechtella tricuspidata (Wu et al 2011), with honey (acting as simulated nectar) increasing survival and decreasing development time. Hence, some spiders appear to be able to use the carbohydrates in nectar to compensate for a lack of overall food availability.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the miturgid spider, Cheiracanthium inclusum , supplementing the diet of food-limited individuals with nectar allows them to achieve growth and reproductive rates comparable to individuals fed higher quantities of prey (Taylor and Pfannenstiel 2009). Similar results have been found in the crab spider Ebrechtella tricuspidata (Wu et al 2011), with honey (acting as simulated nectar) increasing survival and decreasing development time. Hence, some spiders appear to be able to use the carbohydrates in nectar to compensate for a lack of overall food availability.…”
Section: Introductionsupporting
confidence: 82%
“…We had expected carbohydrates to increase growth, but the large benefit of carbohydrates for spider growth (i.e., carbohydrate fed spiders were > 40% heavier than non-carbohydrate fed spiders on the highest protein treatment) was not expected for such an obligate carnivore. Previous studies have found that spiders, especially actively hunting species, will consume nectar in nature and that nectar can increase survival and growth during periods of limited food availability or starvation (Taylor and Pfannenstiel 2009, Wu et al 2011). Our results suggest that carbohydrates may be more than just an energy supplement during periods of starvation and that carbohydrates could be an important component of this actively hunting spider’s diet during development.…”
Section: Discussionmentioning
confidence: 99%
“…[29] has shown that sponge discs soaked in honey solutions can be used for supplementing the diet of spiders. Here we used sponge discs to provide E. culicivora juveniles with opportunity to feed on nectar in the absence of plants.…”
Section: Cold-anthrone Testingmentioning
confidence: 99%
“…Glucophagy in spiders can improve longevity and fitness and affect molting (Taylor and Pfannenstiel, 2009). Wu et al (2011) observed, in laboratory experiments, that the crab spider Ebrechtella tricuspidata (Fabricius) (Thomisidae) significantly spent more time feeding on honey solution (20%) than on water. Moreover, spiders fed on the honey solution significantly showed higher survival rates, shorter developmental time and pre-oviposition period, and laid more eggs than those spiders fed on water only.…”
Section: Introductionmentioning
confidence: 99%